BEYOND CONVENTIONAL GENDER CLASSIFICATION: VISUAL-LAW PERSPECTIVES ON HOW WOMEN-CENTRIC LEGISLATION IMPACTS MEN’S RIGHTS - Pateria , Shivangi; Bedi, Sanjum (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The paper will explore the relations between women centered law and the rights of men by the use of a new field of visual law, which applies visual aids to understand the complexity of legal formations in the shape of diagrams, flow-charts, and data maps. Although past developments in protective laws against women have been beneficial in terms of their development to accommodate systemic inequalities, such laws have tended to be applied within the binary gender categories that pay little attention to the emerging concepts of gender neutrality. This paper redefines important statutory systems, including those that focus on domestic violence, sexual harassment and dowry-related crimes, among others, to demonstrate how the processing of the law, assumptions, and procedural systems can unintentionally influence substantive and procedural rights of men. Using a mapping of the process of the complaint to adjudication, the paper identifies decision nodes graphically where gender assumptions are involved, where rights to liberty, reputation, and due process are at stake. A jurisprudential consideration of landmark cases underscores the conflict of protective intent versus constitutional equality fought out by courts. The issue of comparative visual policy mapping in the international jurisdictions also shows how gender-neutral frameworks can maintain protection without continuing gender biasness.